2018
DOI: 10.3390/molecules23051077
|View full text |Cite
|
Sign up to set email alerts
|

Two New Steroidal Monoglycosides, Anthenosides A1 and A2, and Revision of the Structure of Known Anthenoside A with Unusual Monosaccharide Residue from the Starfish Anthenea aspera

Abstract: Two new polyhydroxysteroidal glycosides, anthenosides A1 (1) and A2 (2), and one previously known steroidal glycoside anthenoside A (3) were isolated from extract of the tropical starfish Anthenea aspera. Structures of 1–3 were determined by analysis of the spectroscopic data as well as chemical transformations. As a result, the structure of anthenoside A has been revised and the structures of 1 and 2 were established. Glycosides 1–3 contain a 2-acetamido-2-deoxy-4-O-methyl-β-d-glucopyranosyl residue, found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…Compounds 113 – 118 were from the starfish Anthenea aspera . Compounds 113 and 114 contain a 2‐acetamido‐2‐deoxy‐4‐ O ‐methyl‐ β ‐ d ‐glucopyranosyl residue, which has not been found previously in the starfish steroidal glycosides . Compound 115 has an unoxidized Δ 22 ‐24‐nor‐cholestane in its structure .…”
Section: Chemical Constituentsmentioning
confidence: 80%
See 1 more Smart Citation
“…Compounds 113 – 118 were from the starfish Anthenea aspera . Compounds 113 and 114 contain a 2‐acetamido‐2‐deoxy‐4‐ O ‐methyl‐ β ‐ d ‐glucopyranosyl residue, which has not been found previously in the starfish steroidal glycosides . Compound 115 has an unoxidized Δ 22 ‐24‐nor‐cholestane in its structure .…”
Section: Chemical Constituentsmentioning
confidence: 80%
“…It was reported that the cancer‐preventive action of 101 is realized through regulation of mitogen‐activated protein kinase (MAPK) signaling pathway . Both compounds 113 and 114 at 50 μ m slightly inhibited cell viability of human cancer T‐47D cells and they inhibited colony formation of human cancer RPMI‐7951 cells and T‐47D cells by 16 % and 40 %, respectively …”
Section: Bioactivitiesmentioning
confidence: 99%
“…The concentrated methanol extract of A. laevigatus was subjected to sequential separation by column chromatography using Amberlite XAD-2 silica gel followed by reversed-phase HPLC on Discovery C18 and YMC-Pack Pro C18 columns to yield four new polyhydroxylated steroids (1−4), along with two known compounds 5 and 6 ( Figure 1). The known polyhydroxylated steroids were identified by analysis of their 1 H-, 13 C-NMR, and ESIMS spectra and comparison with those reported earlier for (24S)-5α-cholestane-3β,5,6β,15α,24-pentaol (5) and related sulfated compounds previously isolated from the starfish Luidia clathrata and Henricia leviuscula [16,17], and (25S)-5α-cholestane-3β,5,6β,15α,16β,26-hexaol (6) from the starfish L. clathrata [18]. The molecular formula of compound 1 was established to be of C 27 H 48 O 7 from the [M + Na] + sodium adduct ion peak at m/z 507.3292 in the (+)HRESIMS spectrum and the [M -H]deprotonated ion peak at m/z 483.3321 in the (-)HRESIMS spectrum ( Figure S1).…”
Section: Structure Elucidation Of Compounds 1−6mentioning
confidence: 99%
“…Elyakov Pacific Institute of Bioorganic Chemistry which celebrated its 55th anniversary in 2019. Continuing our research on biologically active steroid metabolites from the starfish species inhabiting the Vietnamese sea waters [11][12][13][14][15], herein, we describe the results of our investigation of steroid constituents from the methanolic extract of the starfish Anthenoides laevigatus Liao & A.M. Clark, 1989 (order Valvatida, family Goniasteridae), collected off the coastal waters of the Qui Nhon Province, Vietnam. We have isolated and structurally studied four new polyhydroxylated steroids 1−4, along with two previously known related steroids 5 and 6.…”
Section: Introductionmentioning
confidence: 99%
“…Anthenoside A1 (11) inhibited RPMI-7951 cell colony formation, and anthenoside A2 (12) showed a more significant inhibiting effect against colonies of T-47D cells. [27] pustulosa, collected at a depth of 6 m (20°09.030 N; 107°44.359 E). The steroid composition of the extract was also studied, and three known ketosteroids 20-22 and six sterols 23-28 were isolated.…”
Section: Tu Long Bay Near Khuan Lan Islandmentioning
confidence: 99%